Comparison of Post-Operative Pain after Lap Mesh Hernioplasty and Open Mesh Hernioplasty - Rana Shoaib Aslam, Muhammad Hassaan, Jehanzaib Rashid, Assam Arshid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcome of two tension free methods of hernia repair: laparoscopic mesh repair versus open mesh technique in terms of severity of chronic post-operative pain. Material and methods: In this randomized controlled trial, total 100 male patients with inguinal hernia, age between 20-60 years were selected from Department of Surgery, Arif Memorial Teaching Hospital Lahore. Duration of study was 6 months (from April 2021 to October 2021). Chronic pain was compared between the groups. Results: In our study, mean age in group A and B was 41.84+8.92 years and 43.18+8.58 years respectively. Chronic pain was recorded in 4%(n=2) patients in Laparoscopic group (Group-A) and 28%(n=14) patients in Lichtenstein group (Group-B) while 96%(n=48) patients in Laparoscopic group (Group-A) and 72%(n=36) patients in Lichtenstein group (Group-B) had no chronic pain. Difference was significant (P=0.001). Pain intensity shows that 96%(n=48) patients in Laparoscopic group (Group-A) and 16%(n=8) patients in Lichtenstein group (Group-B) had no pain while moderate pain was reported in 4%(n=2) patients and 72%(n=36) patients respectively in Laparoscopic group and Lichtenstein group and severe pain was noted in Group-B as 12%(n=6), p value was 0.001. Group A was subjected to Laparoscopic Mesh repair and Group B hernia was repaired by Lichtenstein repair Conclusion: We concluded that laparoscopic mesh repair versus open mesh technique in terms of severity of chronic post-operative pain, laparoscopic mesh repair is found with significant lower pain. Keywords: Laparoscopic mesh repair, inguinal hernia, open mesh, severity of chronic post-operative pain.